Tandem Mass Tag-Based Quantitative Proteomics Reveals Implication of a Late Embryogenesis Abundant Protein (BnLEA57) in Seed Oil Accumulation in Brassica napus L. - Zhou, Zhongjing; Lin, Baogang; Tan, Jinjuan; Hao, Pengfei; Hua, Shuijin; Deng, Zhiping (Frontiers in Plant Science, 2022)
Enhancing oil content is one of the major goals in Brassica napus breeding, however, genetic regulation of seed oil content in plants is complex and not fully elucidated. In the present study, we report proteins that were differentially accumulated in immature seeds of 35 days after anthesis between two recombinant inbred lines with contrasting seed oil content, HOCL (High oil content line) and LOCL (Low oil content line) using a multiplex isobaric tandem mass tags (TMT)-based quantitative proteomics approach. Over 4600 proteins were quantified in seeds of the two lines, and 342 proteins showed differential accumulation between seeds of HOCL and LOCL. Gene Ontology enrichment analysis revealed that the differentially-accumulated proteins were enriched in proteins involved in lipid biosynthesis and metabolism, photosynthesis, and nutrient reservoir activity. Western blot confirmed the increased abundance of a Late Embryogenesis Abundant protein (BnLEA57) in HOCL seeds compared with LOCL seeds, and over-expression of either BnLEA57 gene or its homology BnLEA55 in transgenic Arabidopsis thaliana enhanced oil content in Arabidopsis seeds. Our work provides new insights into the molecular regulatory mechanism of seed oil content in B. napus.